In vivo relative bioavailability of perfluorooctanoic acid (PFOA) and its alternative hexafluoropropylene oxide trimer acid (HFPO-TA): Influence of food and mechanisms exploration. (October 2022) - Cui, Xinyi; Gu, Qian; Juhasz, Albert; Chen, Yi
Graphical abstract: Abstract: The extensive use of perfluorooctanoic acid (PFOA), and its substitute hexafluoropropylene oxide trimer acid (HFPO-TA) has resulted in their frequent detection in environmental samples. However, little is known of their bioavailability via oral ingestion and the influence of food co-ingestion on absorption. Here, the relative bioavailability (RBA) of PFOA and HFPO-TA in soil was measured using an in vivo mouse model in the presence of food with different nutritional statuses (n = 11). PFOA and HFPO-TA RBA in soil was variable depending on nutrient co-administration, ranging from 29.8–95.5 % and 43.9–68.0 %, respectively. For both PFOA and HFPO-TA, a significantly negative correlation was observed between RBA and protein content in food (r = 0.57–0.72), while a positive correlation was observed with carbohydrate content (r = 0.51–0.57). Mechanistic studies showed that protein in food decreased PFOA and HFPO-TA RBA by down-regulating the expression of fatty acid binding protein 1 (FABP1) and up-regulating the expression of multidrug resistance associated protein 4 (Mrp4) in the liver, which are responsible for the absorption and efflux of PFOA and HFPO-TA. Dietary carbohydrates promoted albumin synthesis and up-regulated FABP1 expression thereby enhancing absorption and increasing PFOA and HFPO-TA RBA. This study provides an insight into potential dietary strategies for reducing exposure to per- and polyfluoroalkyl substances.